Intraindividual Comparison of Everolimus-Eluting Bioresorbable Vascular Scaffolds Versus Drug-Eluting Metallic Stents. (August 2016) - Cassese, Salvatore; Hoppmann, Petra; Kufner, Sebastian; Byrne, Robert A.; Wiebe, Jens; Colleran, Roisin; Giacoppo, Daniele; Harada, Yukinori; Laugwitz, Karl-Ludwig; Schunkert, Heribert; Fusaro, Massimiliano; Kastrati, Adnan
Abstract : Background—: The performance of everolimus-eluting bioresorbable vascular scaffold (BVS) versus drug-eluting metallic stent (DES) in the same individual receiving multilesion percutaneous coronary intervention (PCI) remains poorly studied. This report investigates the intraindividual performance of BVS and DES in patients receiving multilesion PCI and follow-up angiography. Methods and Results—: Data of patients undergoing BVS implantation for de novo lesions from 2012 to 2014 at 2 centers in Munich, Germany, were prospectively collected. Individuals receiving multilesion PCI with BVS and DES and follow-up angiography at 6 to 8 months were studied. Primary end point was in-device late lumen loss. Secondary end points were binary restenosis, target lesion revascularization, and definite stent/scaffold thrombosis. A total of 90 PCI patients with 239 lesions received BVS (n=112) and DES (n=127). Follow-up angiography after a median of 6.6 months (5.8–7.1) showed a higher degree of late lumen loss in lesions treated with BVS versus DES (0.30±0.59 versus 0.22±0.48 mm; P =0.035). However, the adjustment for baseline angiographic imbalances discarded an influence of stent type on late lumen loss ( P =0.82). At the same time point, binary restenosis was comparable between BVS and DES (7.8% versus 8.9%; P =0.90). After a median of 13.2 months (9.2–17.6), target lesion revascularization (9.8% versus 10.2%; P =0.97) and definite stent/scaffold thrombosis (2.7% versus 1.6%; P =0.48) did not differ between BVS and DES. Conclusions—: In patients receiving multilesion PCI, BVS displays acceptable intraindividual performance compared with DES. Larger trials, extended follow-up, and continuous device iteration remain essential to improve BVS technology.